Conformation, Bioactivity and Electrochemical Performance of Glucose Oxidase Immobilized on Surface of Gold Nanoparticles. (10th March 2015) - Song, Yonghai; Chen, Jingyi; Liu, Hongyu; Song, Yonggui; Xu, Fugang; Tan, Hongliang; Wang, Li
Graphical abstract: Here, a series of gold nanoparticles (AuNPs) -glucose oxidase (GOD) nanocomposites, such as AuNPs-GOD, AuNPs-mercaptohexadecyl acid (MHA)-GOD and AuNPs-mercaptoundecanoic acid (MUA)-GOD, have been prepared to study the effects of conformation and bioactivity of GOD on AuNPs and surface chemistry of AuNPs on electroanalytical performance of GOD. The work might provide potential guidance for developing biosensor based on nanomaterials. Highlights: A series of AuNPs- GOD nanocomposites have been prepared. Effect of conformation of GOD/AuNPs on electroanalytical performance of GOD was explored. Effect of bioactivity of GOD/AuNPs on electroanalytical performance of GOD was explored. Effect of surface chemistry of AuNPs on electroanalytical performance of GOD was explored. The work might provide potential guidance for developing biosensor based on nano. Abstract: Since nanomaterials have been extensively used to immobilize enzymes/proteins for developing electrochemical biosensors, it is very important to know the effects of both the conformation and bioactivity of these immobilized enzymes/proteins and the surface condition of the nanomaterials on the electroanalytical performances of enzymes/proteins based biosensors. In this work, a series of gold nanoparticles (AuNPs)-glucose oxidase (GOD) nanocomposites, such as AuNPs-GOD, AuNPs-mercaptohexadecyl acid (MHA)-GOD and AuNPs -mercaptoundecanoic acid (MUA)-GOD, have been prepared to investigate the relationship among the conformation and bioactivity of GOD immobilized on AuNPs, the surface condition of AuNPs and the electroanalytical performance of biosensors. It was found that the conformation and bioactivity of GOD immobilized on AuNPs surface depended on the surface condition of AuNPs and were more or less changed. The direct electrochemistry of GOD became better with the increase of deformation. When AuNPs-GOD nanocomposites were employed to develop glucose biosensor based on the reduction of O2, the MHA and MUA layer around AuNPs seriously disrupted the performance of biosensors. The work might provide a potential guidance for developing biosensor based on nanomaterials and enzymes/proteins.